2013
DOI: 10.1007/s11434-013-5960-6
|View full text |Cite
|
Sign up to set email alerts
|

Sinorhizobium meliloti lsrB is involved in alfalfa root nodule development and nitrogen-fixing bacteroid differentiation

Abstract: Rhizobia interact with host legumes to induce the formation of nitrogen-fixing nodules, which is very important in agriculture and ecology. The development of nitrogen-fixing nodules is stringently regulated by host plants and rhizobial symbionts. In our previous work, a new Sinorhizobium meliloti LysR regulator gene (lsrB) was identified to be essential for alfalfa nodulation. However, how this gene is involved in alfalfa nodulation was not yet understood. Here, we found that this gene was associated with pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 25 publications
(29 reference statements)
0
20
0
Order By: Relevance
“…In our previous work, the lsrB1 -2 and lsrB1 (plasmid insertion) mutants induced heterogeneous, ineffective nodules on alfalfa (19,33). Premature senescence appeared in these nodules, and abnormal bacteroid differentiation was found (33).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In our previous work, the lsrB1 -2 and lsrB1 (plasmid insertion) mutants induced heterogeneous, ineffective nodules on alfalfa (19,33). Premature senescence appeared in these nodules, and abnormal bacteroid differentiation was found (33).…”
Section: Discussionmentioning
confidence: 88%
“…Premature senescence appeared in these nodules, and abnormal bacteroid differentiation was found (33). Correspondingly, oxidative bursts were observed in most defective nodules (33). Therefore, it is possible that LsrB is involved in suppression of the host defense response.…”
Section: Discussionmentioning
confidence: 92%
“…meliloti lsrB1-2 and oxyRsm mutants produces less GSH Both S. meliloti lsrB 1-2 (lsrB in-frame deletion, described in [11]) and gshB1 minus mutants elicited similar, deficient root nodules on alfalfa plants [6], which prompted us to examine the GSH level in the lsrB mutant. Q-TOF LC/MS analysis showed that the level of GSH decreased by 14.28%-18.58% in the lsrB1-2 mutant compared with the wild-type (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial strains and growth conditions Sinorhizobium meliloti 1021, lsrB1-2 [11] and oxyRsm [10] were grown in Luria-Bertani (LB) medium supplemented with 2.5 mM MgSO 4 and 2.5 mM CaCl 2 (LB/MC) at 288C [12]. The following antibiotics were used at the concentrations indicated: chloramphenicol, 10 mg/ml; neomycin, 200 mg/ml; spectinomycin, 100 mg/ml; tetracycline, 10 mg/ ml; and streptomycin, 500 mg/ml.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study, we found that a new Sinorhizobium LysR family transcriptional regulator gene, lsrB , is required for efficient alfalfa nodulation (Luo et al ., ). The nodules induced by a S. meliloti lsrB deletion mutant showed premature senescence, indicating impaired bacteroid differentiation (Tang et al ., ). LsrB directly regulates the expression of genes involved in lipopolysaccharide biosynthesis (Tang et al ., ); this regulator is associated with glutathione production and with induction of katA in an OxyR‐dependent manner (Lu et al ., ).…”
Section: Introductionmentioning
confidence: 97%